ANALYSIS OF CASSIAVERA FARMING DEVELOPMENT STRATEGY IN KERINCI REGENCY - Ulma, Riri Oktari; Nurchaini, Dewi Sri; Effran, Endy (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The purpose of this study are describes general picture of Cassiavera farming in Kerinci Regency, and Identifying any strategies and alternative strategies that can be applied in developing Cassiavera farming in Kerinci Regency. Research data is sourced from primary and secondary data. Data collection techniques are taken by means of observation, in-person interview, and indepth interview. Determination of sample regions is done by the Stratified–Cluster random sampling method, where the technique combines stratafication and cluster methods. Meanwhile, the determination of farmer respondents was taken using the slovin technique. Data analysis in descriptive and SWOT analysis. The results showed that the development of Cassiavera farming in Kerinci Regency uses S-O strategy which is a combination of strength and opportunity factors, with alternative strategies that can be applied, namely maintaining the quality of Cassiavera to maintain the superior advantage of Cassiavera as Indonesia's superior export commodity to meet high market demand.